Four‐dimensional computed tomography (4DCT): A review of the current status and applications. Issue 5 (3rd June 2015) - Kwong, Yune; Mel, Alexandra Olimpia; Wheeler, Greg; Troupis, John M
Summary The applications of conventional computed tomography (CT) have been widely researched and implemented in clinical practice. A recent technological innovation in the field of CT is the emergence of four‐dimensional computed tomography (4DCT), where a three‐dimensional computed tomography volume containing a moving structure is imaged over a period of time, creating a dynamic volume data set. 4DCT has previously been mainly utilised in the setting of radiation therapy planning, but with the development of wide field of view CT, 4DCT has opened major avenues in the diagnostic arena. The aim of this study is to provide a comprehensive narrative review of the literature regarding the current clinical applications of 4DCT. The applications reviewed include both routine diagnostic usage as well as an appraisal of the current research literature. A systematic review of the studies related to 4DCT was conducted. The Medline database was searched using the MeSH subject heading 'Four‐Dimensional Computed Tomography'. After excluding non‐human and non‐English papers, 2598 articles were found. Further exclusion criteria were applied, including date range (since wide field of view CT was introduced in 2007), and exclusion of technical/engineering/physics papers. Further filtration of papers included identification of Review papers. This process yielded 67 papers. Of these, exclusion of papers not specifically discussing 4DCT (cone beam, 4D models) yielded 38 papers. As part of the review, the technique for 4DCT is described, with perspectives as to how it has evolved and its benefits in different clinical indications.